Management of Infectious Solid Medical Waste at Hospital X Surabaya - Vio Firdatus Vanesa Firdatus Vanesa; Ferry Kriswandana; Putri Arida Ipmawati; Suprijandani Suprijandani; Iva Rustanti Eri Wardoyo; Christine Inventor Reyes (International Journal of Advanced Health Science and Technology, 2024)
The hospital played a crucial role in treating health conditions and had the potential to cause negative impacts through generated medical waste. Based on the preliminary survey conducted, it was found that the management of infectious solid medical waste at Rumkital Dr. Oepomo Surabaya did not meet the requirements for containment, transportation, temporary storage, human resources, and infrastructure. Based on these issues, this study aimed to describe the management of infectious solid medical waste at Rumkital Dr. Oepomo in 2024. The method used was descriptive with a cross sectional approach. Data was collected through direct observation of the management of infectious solid medical waste. Information was also obtained through interviews with infectious solid medical waste management officers. In addition, the volume of infectious solid medical waste was measured directly in the field. The data obtained was compared with Minister of Health Regulation Number 2 of 2023. The results of this study indicated that the volume of infectious solid medical waste generated at Rumkital Dr. Oepomo Surabaya over 7 days was 5.34 kg/day. The assessment of the management process for infectious solid medical waste found that the containment, transportation, and temporary storage processes did not meet the requirements. The evaluation of supporting factors for managing infectious solid medical waste including human resources and facilities also did not meet the criteria. The conclusion was that the management process of infectious solid medical waste at Rumkital Dr. Oepomo Surabaya did not fully meet the requirements. The recommendations that can be given were as follows in the containment process medical waste should not exceed ¾ of its maximum volume and should be tied into a single braid, transportation should use trolleys, and temporary storage should involve the use of freezers. Supporting factors in waste management include the need for personnel to undergo training in medical waste handling and the procurement of complete PPE facilities for waste management personnel.